2019
DOI: 10.1002/prp2.487
|View full text |Cite
|
Sign up to set email alerts
|

l‐α‐Lysophosphatidylinositol (LPI) aggravates myocardial ischemia/reperfusion injury via a GPR55/ROCK‐dependent pathway

Abstract: The phospholipid l‐α‐lysophosphatidylinositol ( LPI ), an endogenous ligand for GPR 55, is elevated in patients with acute coronary syndrome, and a GPR 55 antagonist cannabidiol ( CBD ) reduces experimental ischemia/reperfusion (I/R) injury. While LPI activates multiple signaling pathways, little is known about which ones are important in cardiomyocytes. In this study we explored whether activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Moreover, high levels of LPI have been related with a poor outcome in acute myocardial infarction. 28 Nevertheless, the specific role of this LPI in necrosis still has to be explored with other techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high levels of LPI have been related with a poor outcome in acute myocardial infarction. 28 Nevertheless, the specific role of this LPI in necrosis still has to be explored with other techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that the inhibition of Ca 2+ signaling underlies the negative inotropic effects of CBD in myocytes, presenting a reduction in maximal shortening amplitudes with no alteration of the time course of contraction. However, Robertson-Gray et al [23] observed a cardioprotective effect of CBD against l-α-lysophosphatidylinositol (LPI), an endogenous ligand of G protein-coupled receptor 55 (GPR55), a putative cannabinoid receptor, which is also elevated in patients with the coronary syndrome. The injury was decreased by CBD acting as an antagonist of the GPR55 receptor.…”
Section: Cardiovascular Effects Of Cbd Observedmentioning
confidence: 99%
“…In Ca 2+ homeostasis, CBD causes the inhibition of L-type Ca 2+ channels, impeding the internalization of additional Ca 2+ from the interstitial medium. When coupled with a reduction in the IP 3 -mediated release of Ca 2+ from the sarcoplasmic reticulum, it results in difficulty depolarizing the cellular membrane, restraining the triggering of the myocyte action potential [23]. In pathological conditions involving high extracellular K + , CBD can modulate the activation of the Na + /Ca 2+ exchanger (NCX) to release additional Ca 2+ from the cytosol into the extracellular space [33].…”
Section: Vasorelaxationmentioning
confidence: 99%
“…77 The theoretical contribution of these noncannabinoid GPRs to the genesis of cannabinoid-induced cardiac arrhythmias and ACS may be from alteration of endothelial vasoregulation and membrane cation currents of the cardiac conduction system. 78…”
Section: G Protein-coupled Receptorsmentioning
confidence: 99%